2019
DOI: 10.3389/fonc.2019.01277
|View full text |Cite
|
Sign up to set email alerts
|

Sustain, Adapt, and Overcome—Hypoxia Associated Changes in the Progression of Lymphatic Neoplasia

Abstract: Irregular perfusion and related tissue hypoxia is a common feature of solid tumors the role of which in the survival and progression cancer has been gradually recognized. Adaptation and selection mechanisms in hypoxic areas in solid tumors are regulated by Hypoxia Inducible transcriptional factor 1 (HIF1) and other hypoxia mediators and are associated with aggressive clinical behavior in a large spectrum of malignancies. Aggressive forms of lymphatic neoplasias present with solid tumor-like features, also incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…The environment in which lymphoma cells are found in the human body has different levels of oxygenation. Lymphatic tissues show a lower concentration of oxygen than blood (0.6-2.8% of oxygen) [1,2], while the oxygen concentration in bone marrow counts for approximately 1.3-4.2% [3]. Indeed, secondary lymphoid organs, such as the spleen, may also encounter a hypoxic environment (0.5-4.5% of oxygen) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The environment in which lymphoma cells are found in the human body has different levels of oxygenation. Lymphatic tissues show a lower concentration of oxygen than blood (0.6-2.8% of oxygen) [1,2], while the oxygen concentration in bone marrow counts for approximately 1.3-4.2% [3]. Indeed, secondary lymphoid organs, such as the spleen, may also encounter a hypoxic environment (0.5-4.5% of oxygen) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the TME is characterized by hypoxia [ 13 ]. Indeed, the local imbalance of O 2 consumption and supply results in the development of adaptive strategies/mechanisms that promote cell survival and progression to metastatic phenotype [ 14 ]. Among the above adaptive strategies, hypoxia triggers the expression of carbonic anhydrases (CAs) [ 15 ], a family of metalloenzymes which catalyze the reversible hydration of CO 2 to HCO 3 − and H + .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of SDHD gene lead to overaccumulation of hypoxia inducible factor (HIF) via succinic acid accumulation, followed by promotes angiogenesis and cell proliferation. In recent study, HIF1 is reported to play a dominant role in follicular B-cell maturation and mediate cell growth and aggressive clinical behavior in lymphatic neoplasia [ 21 ]. This raises a possibility that pseudohypoxic genomic mutation may lead to hematological malignancy.…”
Section: Discussionmentioning
confidence: 99%